Konseptualisasi Akhlak Ekonomi Digital: Perspektif Kitab Tarbiyatul Aulad fil Islam Menghadapi Perilaku Konsumtif di Era Digital - Azka Nazan Maulana; Tiana Jati Pandini; Zhahra Putri Rosidy; Dimyati Dimyati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
The disruption of the digital economy in Indonesia has triggered a serious crisis in family morality, characterized by the phenomenon of flexing culture and the increasing divorce rate caused by economic pressures in the digital era. This study aims to analyze the impact of deviant digital economic behavior on marital stability and to formulate a prevention model based on character education. The research employed a qualitative method with a library research approach using a conceptual framework. The primary data source was Tarbiyatul Aulad fil Islam by Abdullah Nashih Ulwan, while secondary data included national statistical reports and relevant journal articles. Data were analyzed using descriptive-analytical content analysis techniques. The findings indicate that internet penetration, which reached 221.5 million users in 2024, is directly proportional to the growing financial vulnerability of families, with economic factors contributing to 104,654 divorce cases nationwide. This issue is further aggravated by emerging external conflicts involving illegal online lending and disguised online gambling activities. Such manipulative financial behaviors violate the principle of Hifzh al-Mal (the preservation of wealth) and undermine household tranquility (sakinah). As a solution, this study proposes the “Digital Economic Morality” model through the revitalization of the family’s role as Madrasatul Ula (the first school), emphasizing the values of Amanah (trustworthiness and transparency) and Qana’ah (contentment). The integration of classical Islamic parenting values with the 3C approach (Contextual, Collaborative, and Consistent) can serve as a spiritual “navigation system” to mitigate the risks posed by digital consumerism algorithms and support the realization of the Indonesia Emas 2045 vision.